Peranan Etika Dalam Meningkatkan Kinerja Public Service - Viqy Andrian Ningsih; Tefani Yelzah Putri; Azzahra Ulhusna; Ahmad Fauzi; Yulia Hanoselina; Rahmadhona Fitri Helmi (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
Ethics in its implementation is used as a guideline or regulation of governance in government. In addition, ethics are also the basis for administrators in organizing public services. Although violations or misappropriations of ethics still occur frequently. Therefore, the cultivation and understanding of moral and ethical values is very important in every individual government apparatus. So it can also be known that the ethics possessed by every government apparatus also determines the success of a nation in prospering the community. In public administration, in order for services to run well, government officials need to apply the correct ethics in accordance with the codes of ethics that have been set by the government. Work ethics can improve employee performance by training employees to behave well in work situations. This study uses a literature study research method carried out by the method of collecting library data, reading and recording, as well as processing objectively, systematically, analytically, and critically about how the role of ethics in improving public service performance. Ethics exerts influence by improving the government's performance in providing services to the community. Ethics also serves as a moral guideline and is one of the important elements in improving government performance so as to help the government achieve good governance and improve public welfare.